The profiles of English medium instruction teachers in higher education. (4th May 2021) - Macaro, Ernesto; Sahan, Kari; Rose, Heath
Abstract: The global growth of English Medium Instruction (EMI) in higher education and international mobility of faculty and students necessitates that we better understand commonalities of teachers in these emerging contexts. This paper reports on a survey of 461 EMI university lecturers from more than eight countries which attempted to discern the various profiles of EMI teachers at an international level. Data explored teachers' disciplines, age, experience, professional development, teaching contexts, and the role of English proficiency in their professional capacity. Results revealed statistically significant differences in profiles according to the disciplines and country of residence of the teachers. For example, teachers in the Natural Sciences and those in Spain were more likely to report having opportunities for teacher training and EMI certification. Özet: Yükseköğretimde İngilizcenin eğitim dili olarak yaygınlaşması ile birlikte öğretmen ve öğrencilerin uluslararası hareketliliği, ortaya çıkan bu bağlamlarda öğretmenlerin ortak yönlerini daha iyi anlamamızı gerektirmektedir. Bu makale, sekizden fazla ülkeden 461 üniversite öğretim elemanının katıldığı anket verisine göre, eğitim dili olarak derslerinde İngilizce kullanan öğretim elemanlarının farklı profillerini uluslararası seviyede araştırmayı amaçlamaktadır. Veriler; öğretmenlerin disiplinlerini, yaşlarını, deneyimlerini, mesleki gelişimlerini, öğretim bağlamlarını ve mesleki kapasitelerinde İngilizce yeterliliğinin rolünü ele almıştır. Araştırmanın bulguları, disiplinlere ve öğretmenlerin ikamet ettikleri ülkeye göre profillerde istatistiksel olarak anlamlı farklılıklar ortaya çıkarmıştır. Örneğin, doğa bilimleri alanında çalışan ve İspanya'da yer alan öğretim elemanları, öğretmen eğitimi ve eğitim dili olarak İngilizce sertifikası için daha fazla fırsatlara sahip olduklarını bildirmişlerdir.